Aesthetic perceptions of lesbian women about sex shop products (DAPesquisa, 2021)
This article seeks to understand the aesthetic perceptions of lesbian women about sex shop products. Thus, this is an exploratory, basic and descriptive research, which was developed from field research with interviews, using a semi-structured questionnaire. This questionnaire was applied to focus groups, both online and in person, and the analysis of these data was carried out in a qualitative way. In the case of this study, it was possible to identify that the aesthetic perceptions of lesbian women about sex shop products follow from a relationship of power with the partner to a relationship of strangeness with the object, generating possible discomfort. Still, both in online research and in face-to-face research, it was possible to identify that there is a preference for phallic sex toys with artificial colors and shapes.
Keywords: Sex toys; Lesbians; Sex-oriented businesses; Pattern perception